(untitled) (Eurasian Medical Research Periodical, 2023)
In daily clinical practice, the problems of breast mass, pain or discharge is extremely common in the Iraqi population, as well as, globally. Nearly all patients develop fear about the possibility of malignancy when they acquire a breast mass. However, the trend in most health care institute is that most breast lesion are of benign biologic behavior and among true neoplastic lesions, the rate of malignancy is somewhat low. Marital status has been linked to outcome of breast malignancy; however, the link is controversial